(untitled) - Saladin, Kenneth S. (Boston, 2014)
This distinctive text was developed to stand apart from all other anatomy texts with an approach borne out of more than 30 years of teaching, unparalleled art, and a writing style that has been acclaimed by reviewers. Designed for a one–semester college anatomy course, Saladin requires no prior knowledge of chemistry or cell biology.
Keywords: Human anatomy,Cơ thể con người